Primitive reflexes as behavioral biomarkers of cognitive aging: associations with physical activity and resilience—a pilot study - Horváth-Pápai, Anna; Tóth, Eliza Eszter; Barthalos, István; Alföldi, Zoltán; Takács, Johanna; Ihász, Ferenc (Frontiers in Aging Neuroscience, 2025)
IntroductionPrimitive reflexes (PRs) are brainstem-mediated automatic responses that typically disappear in early life, but may reappear in older age, which may be associated with neurodegenerative processes. But the presence of PRs in cognitively healthy adults has not yet been sufficiently explored. The relationship between PRs and cognitive functioning (COG) may be influenced by modifiable factors such as physical activity (PA) and psychological resilience. This cross-sectional observational pilot study aimed to investigate the mediating and moderating role of physical activity and resilience in the association between primitive reflexes and cognitive functioning in older adults.MethodsA total of 30 older adults (mean age 73.4 ± 6.9 years; 80% female) living in residential care facilities were assessed. PRs were evaluated using standardized neurological protocols, COG was measured with the Mini-Mental State Examination, PA with the Global Physical Activity Questionnaire, and resilience with the Connor–Davidson Resilience Scale. Moderation and mediation models were tested using Hayes’ PROCESS macro, controlling for age and BMI.ResultsA higher number of primitive reflexes was strongly associated with lower cognitive functioning [COG (r = −0.904, p < 0.001)]. Physical activity showed a significant mediating effect in this association, indicating that more active older adults exhibited better cognitive performance despite the presence of primitive reflexes. Resilience, although correlated with both cognition and physical activity, did not show a mediating or moderating effect.DiscussionThese findings highlight primitive reflexes as potential behavioral biomarkers of cognitive aging, and underscore the importance of physical activity as a protective factor that may buffer against neurocognitive decline.